Bituminaria kyreniae (Fabaceae), a new species from Northern Cyprus - Giusso Del Galdo, Gianpietro; Brullo, Cristian; Brullo, Salvatore; Cambria, Salvatore; Minissale, Pietro (Phytotaxa, 2015)
Bituminaria kyreniae is described and illustrated as a new species to science from northern Cyprus. It is an obligate chasmophyte growing on the south-facing carbonatic cliffs of Kyrenia range. Diagnostic morphological features, micro-morphology of pod and seed testa, ecology, conservation status, and chorology of the new species are provided. Besides, its relationships with the currently recognized species belonging to the genus Bituminaria are also examined.